Growth, survival and peptidolytic activity of Lactobacillus plantarum I91 in a hard-cheese model - Bergamini, Carina Viviana (2013)
In this work, we studied the growth, survival and peptidolytic activity of Lactobacillus plantarum I91 in a hard-cheese model consisting of a sterile extract of Reggianito cheese. To assess the influence of the primary starter and initial proteolysis level on these parameters, we prepared the extracts with cheeses that were produced using two different starter strains of Lactobacillus helveticus (Lh138 or Lh209) at three ripening times: 3, 90 and 180 days. The experimental extracts were inoculated with Lb. plantarum I91; the control extracts were not inoculated, and the blank extracts were heat-treated to inactivate enzymes and were not inoculated. All extracts were incubated at 34ºC for 21 days, and then the pH, microbiological counts and proteolysis profiles were determined. The basal proteolysis profiles in the extracts of young cheeses made with either strain tested were similar, but many differences between the proteolysis profiles of the extracts of the Lh138 and Lh209 cheeses were found when riper cheeses were used. The pH values in the blank and control extracts did not change, and no microbial growth was detected. In contrast, the pH value in experimental extracts decreased, and this decrease was more pronounced in extracts obtained from either of the young cheeses and from the Lh209 cheese at any stage of ripening. Lb. plantarum I91 grew up to 8 log during the first days of incubation in all of the extracts, but then the number of viable cells decreased, the extent of which depended on the starter strain and the age of the cheese used for the extract. The decrease in the counts of Lb. plantarum I91 was observed mainly in the extracts in which the pH had diminished the most. In addition, the extracts that best supported the viability of Lb. plantarum I91 during incubation had the highest free amino acids content. The effect of Lb. plantarum I91 on the proteolysis profile of the extracts was marginal. Significant changes in the content of free amino acids suggested that the catabolism of free amino acids by Lb. plantarum I91 prevailed in a weakly proteolysed medium, whereas the release of amino acids due to peptidolysis overcame their catabolism in a medium with high levels of free amino acids. Lb. plantarum I91 was able to use energy sources other than lactose to support its growth because equivalent numbers of cells were observed in extracts containing residual amounts of lactose and in lactose-depleted extracts. The contribution of Lb. plantarum I91 to hard-cooked cheese peptidolysis was negligible compared to that of the starter strain; however, its ability to transform amino acids is a promising feature of this strain.